The Impact of Distributive Justice Perceptions on Alternative Work Arrangement Participation Intentions in Public Accounting - McGowan, Josh; Knight, Margaret; Frazier, M. Lance (STIE Malangkucecwara, 2024)
Turnover and staffing issues are consistently ranked among public accounting firms' most critical issues, but the post-COVID-19 work environment adds new and unique challenges. Now that employees have experienced remote work, many do not want to return to the office. However, if employees do not believe they can be successful using a flexible work arrangement at their current firm, they may go elsewhere. The need for successful flexible work programs is exacerbated by the declining interest in the accounting profession, which is increasing the accounting labor shortage and making competition for talent even greater. Accounting firms need to understand what factors impact an employee’s decision to participate in an alternative work arrangement (AWA). This study explores factors that impact AWA participation intentions using organizational justice perceptions. Using a sample of 135 public accountants, distributive justice perceptions surrounding AWAs were found to be positively related to AWA participation intentions. This finding extends the current AWA literature and provides valuable information to public accounting firms. This result informs firm leaders about the importance of equitable career outcomes when employees are considering AWAs. Firms can leverage this insight to ensure performance evaluation metrics focus on specific, measurable employee outputs, which should help ensure that work-related outcomes are consistent between employees regardless of their work arrangement.